Comparative efficacy of Chinese herbal injections in patients with cardiogenic shock (CS): a systematic review and Bayesian network meta-analysis of randomized controlled trials - Yue, Linkai; Xiao, Lu; Zhang, Xuemin; Niu, Liqing; Wen, Yue; Li, Xiaowei; Wang, Ying; Xing, Guanghe; Li, Guiwei (Frontiers in Pharmacology, 2024)
Background: Cardiogenic shock (CS) is the primary cause of death in patients suffering acute myocardial infarction. As an emerging and efficacious therapeutic approach, Chinese herbal injections (CHIs) are gaining significant popularity in China.However, the optimal CHIs for treating CS remain uncertain.We searched eight databases from inception to September 30, 2023. Subsequently, we conducted the Bayesian network meta-analysis (NMA). Interventions were ranked based on the surface under the cumulative ranking curve (SUCRA) probability values. To compare the effects of CHIs on two distinct outcomes, a clustering analysis was performed. Furthermore, the quality of the studies was assessed.Results: For the study, we included 43 RCTs, encompassing 2,707 participants. The study evaluated six herbal injections, namely Shenfu injection (SF), Shengmai injection (SM), Shenmai injection (Sm), Danshen injection (DS), Huangqi injection (HQ), and Xinmailong injection (XML). The analysis findings suggested that Sm (MD = -1.05, 95% CI: -2.10, -0.09) and SF (MD = -0.81, 95% CI: -1.40, -0.25) showed better efficacy compared to Western medicine (WM) alone in reducing in-hospital mortality. The SUCRA values revealed that Sm + WM ranked first in terms of in-hospital mortality, cardiac index (CI), and hourly urine output but second in improving left ventricular ejection fraction (LVEF) and mean arterial pressure (MAP). SF + WM, however, had the greatest impact on raising the clinical effective rate. In MAP, SM + WM came out on top. Moreover, in terms of safety, only 14 studies (31.8%), including five types of CHIs: SF, Sm, SM, HQ, and XML, observed adverse drug reactions.To summarize, this analysis discovered that, in terms of patients suffering from CS, CHIs + WM yielded significantly greater advantages than WM alone. Based on in-hospital mortality and the remaining outcomes, Sm performed excellently among all the involved CHIs.